(untitled) (BIRDEM Medical Journal, 2020)
Background: Nutritional rickets has emerged as a public health problem in Bangladesh during the past two decades, with up to 8% of children being clinically affected in some areas. Insufficiency of vitamin D and dietary calcium is thought to be the underlying cause. Vitamin D administered with or without calcium is commonly regarded as the mainstay of treatment. Calcium alone or in combination with vitamin D has also been used in the treatment of nutritional rickets. So this study was done to assess the effects of vitamin D, calcium or combination of vitamin D and calcium for the treatment of nutritional rickets in Bangladeshi children. Methods: This open labeled randomized comparative study was done in the Department of Paediatrics, Sylhet MAG Osmani Medical College Hospital from July 1, 2010 to June 30, 2012 A total 48 rickets patient was enrolled in this study. After selection of cases patients were divided in to three groups by lottery method. Group A received single i/m dose of vitamin D 4,00,000 IU (2,00,000 IU in each buttock), Group B received calcium (750 mg per day) for 6 weeks and Group C received both calcium (750 mg per day) for 6 weeks and single i/m dose of vitamin D 4,00,000 IU (2,00,000 IU in each buttock). Response was evaluated by serum alkaline phosphatase level and using 10-point radiographic score developed by Thacher and colleagues at baseline, 6 weeks, and 12 weeks. Results: Mean age of the study participants was 35.83 months. Male to female ratio was 2:1. The radiographic score was significantly improved in first and second follow up (p<0.001) in all groups. But there was significant difference of improvement in Group C than Group A and Group B. In Group C, the percent reduction from base to first follow up was 80.05±7.04 and 90.65±3 in second follow up which showed quick improvement in combination therapy. Serum alkaline phosphatase also significantly reduced in all three groups. Conclusion: Combination use of vitamin D and calcium in the treatment of nutritional rickets is more effective than prescribing either vitamin D or calcium alone. Birdem Med J 2021; 11(1): 39-46